Institutional linkages and landscape governance systems: The case of Mt. Marsabit, Kenya - Robinson, Lance W.; Kagombe, J.K. (Resilience Alliance, Inc., 2018)
The desire to overcome fragmented management of the natural ecosystems on which human beings depend has contributed to a growing interest in landscape approaches and to deeper questions about landscape governance systems. We assessed the emergent governance system that corresponds to the Mt. Marsabit landscape ecosystem in northern Kenya, applying a framework that includes 17 different indicators. We found that in this governance system, the most important spaces where coordination and joint planning took place were district level coordination committees, within which representation of communities and voices from the grassroots was poor. Institutional and organizational linkages were such that those parts of the governance system for which legitimacy and accountability were strongest were the parts for which ability to generate resources was weakest, while the parts of the governance system that had the best access to resources was where accountability was weakest or the most indirect. In this paper we use the Mt. Marsabit case study to explore the role that organizational and institutional linkages play in the strengths and weaknesses of landscape governance systems, and consider the implications for governance design at landscape level. Institutional linkages play a critical role in determining how landscape governance systems function across scales and levels, and their degree of fit. Appropriate linkages can help to create connections among key dimensions of effective governance within the system, dimensions such as use of knowledge, capacity to generate resources, fit, learning, legitimacy, accountability, and responsiveness, strengthening the system as a whole. Of the various linkages that characterize a governance system, it is those that give community-level actors a meaningful voice at higher levels and in spaces where key decisions are being made that are most critical for enabling effective landscape governance.